7 Simplifying
75 = 11x + -2
Reorder the terms:
75 = -2 + 11x
Solving
75 = -2 + 11x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-11x' to each side of the equation.
75 + -11x = -2 + 11x + -11x
Combine like terms: 11x + -11x = 0
75 + -11x = -2 + 0
75 + -11x = -2
Add '-75' to each side of the equation.
75 + -75 + -11x = -2 + -75
Combine like terms: 75 + -75 = 0
0 + -11x = -2 + -75
-11x = -2 + -75
Combine like terms: -2 + -75 = -77
-11x = -77
Divide each side by '-11'.
x = 7
Simplifying
x = 7